ALTERNATIF PENYEDIAAN PAKAN DENGAN PENERAPAN BUDIDAYA HMT ORGANIK, TEKNOLOGI PENGOLAHAN HIJAUAN DAN LIMBAH PERTANIAN PADA SENTRA PRODUKSI SAPI POTONG DI KABUPATEN MANOKWARI - F. R. Pawere; L.Y. Sonbait (Buletin Udayana Mengabdi, 2016)
Feeding the cattle, in beef cattle production centers in Masni District Manokwari Regency is less efficient.Excess of feed is usually thrown away or burned. The purpose of this community service is to train farmersto build forage fodder gardens for providing feed for cattle. The feed waste is processed using Biogastechnology to be forage fodder gardens fertilizer. By using feed processing technology, it can make silage,ammoniation and hay. The results of community service were farmers already have their own fodder gardens,breeders can make silage, ammoniation and hay as an alternative feed when feed is very difficult to obtain,especially during the dry season.